Folic Acid Supplementation can Reduce the Risk of Neural Tube Defects in Fetus - Rofi'atunnisa' Rofi'atunnisa' (Jurnal Penelitian Perawat Profesional, 2020)
Neural tube defects are among the abnormalities in the fetus that most often occur after heart defects and abnormalities in the genitourinary system. The causes of neural tube accidents are generally multifactorial. One of the causes of neural tube defects is a folic acid deficiency. Folic acid is essential for embryological development during pregnancy. Most cases of folic acid deficiency often go undiagnosed. Many pregnant women do not realize that they have a folic acid deficiency. The purpose of this paper is to examine the effect of folic acid supplementation on reducing the risk of neural tube defects in the fetus. This study uses the literature review method with searches sourced from the NCBI database, the researcher only captures articles published in the period between 2010 - 2020. Of all the articles obtained, 25 selected articles were analyzed using the systematic literature review method by comparing it from the title, approach, objectives, results, and discussion, then analyzed and arranged systematically. From several sources that have been found, it is stated that folic acid supplementation can reduce the risk of neural tubes in the fetus.